1984
DOI: 10.1063/1.864576
|View full text |Cite
|
Sign up to set email alerts
|

Stability studies of a hollow plasma in the double cusp experiment

Abstract: Axisymmetric cusp end cells have application for the stabilization and plugging of a tandem-mirror-type reactor. Experiments have been performed on the RFC-XX double cusp in Nagoya, Japan to measure the stability of the hollow plasma in the adiabatically confined region of the device. Experiments were performed with both a uniform field central section and with a mirror central section connecting the two cusps. The plasma is produced by an rf discharge of gas puffed into the vessel. Plasma fluctuations were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…We observed fluctuations of plasma density and potential which were related to the hollow density profile in the cusp region [12]. These fluctuation levels were sensitive to the gas puffing rate.…”
Section: Fig 5 Plasma Density In Central Section In M = -1 Mode As a ...mentioning
confidence: 81%
“…We observed fluctuations of plasma density and potential which were related to the hollow density profile in the cusp region [12]. These fluctuation levels were sensitive to the gas puffing rate.…”
Section: Fig 5 Plasma Density In Central Section In M = -1 Mode As a ...mentioning
confidence: 81%
“…( 4) for the specific case of the modified tandem cusp plasma. As pointed out, the pressure and density profiles are hollow as verified by the recent experiments on RFC-XX [15]. The inner field lines near the magnetic field null have bad curvature and are therefore unstable.…”
Section: _ J 1_ 2 A) + Oj Dr M+1 C Imentioning
confidence: 55%
“…In conclusion, the present calculations have shown that a radial ponderomotive force can stabilize the hollow plasma profiles in the RFC-XX double-cusp experiment by doubling the RF power already available, and that the preferred mode is an m = 0 ion cyclotron wave. Comparison of the theory with experimental results is not possible at this time because the results so far indicated the absence of flute instabilities for other reasons [15]. Future work on this problem should address the hot-plasma effects, especially the existence of parallel electric fields and the accompanying radial ponderomotive force on the electrons.…”
Section: Stabilization Calculationsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is known from experiments on divertor stabilization of mirror devices [47][48][49] and on cusps [10,50] that the plasma pressure decreases monotonically towards the magnetic separatrix (towards the increasing of ∫dl/B) in a somewhat steeper manner than follows from MHD. There can be additional plasma containment [48] or losses [10] at internal regions with field nulls that depends on plasma generation.…”
Section: Resultsmentioning
confidence: 99%